STRATEGI PENGEMBANGAN UNIT USAHA ROTI NEW CAMPUS POLITEKNIK NEGERI LAMPUNG - Sarono Sarono (Industrika : Jurnal Ilmiah Teknik Industri, 2017)
Bread can be found in various food outlets as bakeries, departement stores, stalls, vending sellers or canteens of school and campus. In Bandar Lampung, some bread is produced by small units of bakery either by individual or joint business. The research is aimed at learning some problems of product marketing and some aspects significantly influencing the marketing strategyof the new campus bakery. The research shows that the internal factor evaluation analysis value was at 2,564 that indicate medium value, while the external factor evaluation analysis was at 2,265 which indicate medium value. The internal-external analysis shows that the bakery was at V position, strategy can do in these conditions is market penetration and product development. Strength, weaknesses, oppourtunities, and threats analysis found that the bakery apply 11 businnes strategies developed based on the internal factors – the strengt and weaknesses – as well as the external factors – the opportunities and threat. Keywords: bread, development strategy, SWOT